Implementation of Drug Logistics Management in Disaster Preparedness at Tipo Public Health Center Palu City - Muhammad Rizki Ashari; Miftahul Haerati Sulaiman; Firmansyah Firmansyah; Mohammad Ilham; Muhammad Nasir (Buletin Penelitian Kesehatan, 2026)
Background: Effective drug logistics management is essential to ensure the availability, continuity, and timely distribution of medicines, particularly in disaster-prone areas. Tipo Public Health Center in Palu City faces challenges related to essential drug availability, procurement delays, and stock discrepancies, which may affect routine services and disaster preparedness.Methods: This study used a qualitative case study design. Data were collected through in-depth interviews, observation, and document review. Informants included the person in charge of the pharmaceutical unit, the head of the Public Health Center, and pharmaceutical staff. Data validity was strengthened through source and method triangulation, and data were analyzed using content analysis.Results: Drug logistics planning was conducted periodically based on stock evaluation, previous drug use, disease patterns, and estimated patient needs. The process involved collaboration among pharmacists, pharmaceutical staff, health workers, epidemiology personnel, and management. However, several challenges were identified, including uncertainty in patient numbers and disease trends, limited stock availability at the Health Office pharmaceutical warehouse, discrepancies between requested and received medicines, and technical problems in the e-catalogue system. Disaster preparedness was integrated through emergency stock considerations, although contingency planning and coordination still require strengthening.Conclusion: Drug logistics management at Tipo Public Health Center has been implemented through collaborative and needs-based planning, but procurement constraints, stock mismatches, and technological barriers reduce its effectiveness. Strengthening coordination, improving digital infrastructure, and developing clear emergency drug contingency plans are necessary to support routine services and disaster preparedness.